Sexual dimorphism and the placenta – results from the ROLO kids study. (2nd November 2022) - Donnelly, Jean M. T.; Horan, Mary; Segurado, Ricardo; Mooney, Eoghan E.; French, Shannon; Molloy, Eleanor J.; McAuliffe, Fionnuala M.
Abstract: Background/Aims: To assess the association between placental morphology and neonatal and infant anthropometry, including analysis by sex. Study Design: Data from the ROLO Kids [Randomized COntrol Trial of LOw Glycaemic Index in Pregnancy] study were analyzed including placental weight and morphology. Placental, anthropometric and skinfold measurements were recorded as markers of adiposity in 196 neonates and 215 infants at 6 months of age. Ratios including subscapular-to-triceps skinfold ratio and waist-to-height ratio were used as markers of central adiposity, while the sum of all skinfolds and subscapular plus triceps skinfolds were used as markers of general adiposity. Analysis was performed for total groups and by sex. Results: On simple linear regression placental weight was associated with neonatal and infant anthropometric measurements. On multiple regression, the placental weight was associated with birth weight. In the neonatal period placental weight was associated with general adiposity in males only (sum of skinfolds ( B 0.007, p < .001) and subscapular + triceps skinfolds a marker of general adiposity ( B 0.004 p < .001)). At 6 months of age placental length was positively associated with central adiposity in the total group ( B 0.006, p .036) and maximum cord diameter was inversely associated with infant central adiposity ( B − 0.309 p .043) in males only. Conclusion: The placental phenotype is associated with anthropometry at birth and this association persists to early infancy with a stronger relationship noted in this cohort amongst males. This suggests sexual dimorphism may play a role in the impact of the placenta on infant anthropometry.